Paragraph and Its Development Pattern On The Essay Writing Of Elementary School Students - Herman Budiyono (Universitas Jambi, Magister Program of English Education Department, 2020)
This study aimed to describe the quality of the paragraph and its development pattern in the essay writing of elementary school (Sekolah Dasar – SD) students in Jambi City (Kota Jambi – KJ) (SD-KJ). This study utilized a